Broadcom’s Acquisition of VMware: Opportunities for Partners and Customers - Rai, Lenyatsa Swati; Kim, Ubisi Dongkyu; Hanan, Masilo (Journal of Global Economy, Business and Finance, 2025)
This study examines the repercussions and implications of Broadcom's acquisition of VMware on clients and partners in relation to virtualization and cloud computing adoption. The paper illuminates VMware's significance and Broadcom's underlying strategic objectives in the acquisition, and then delves into the alterations in licensing agreements and channel partner programs. The increased licensing fees and migration alternatives pose challenges for consumers and hosts, necessitating cautious negotiations. Public cloud providers are poised to capitalize on this situation, endeavoring to attract VMware users with competitive pricing, streamlined migration tools, and cutting-edge modernization blueprints. The potential absence of specific VMware tools evokes concerns and prompts inquiries about alternative open-source and commercial solutions. Remaining informed about industry trends and best practices empowers VMware users with essential knowledge to confidently navigate platform shifts and mergers. This article is significant because it provides critical insights into how Broadcom's acquisition of VMware will reshape the virtualization and cloud computing industry, affecting licensing practices, partner dynamics, and customer strategies.